2020
DOI: 10.1101/2020.05.12.20098699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unequal impact of structural health determinants and comorbidity on COVID-19 severity and lethality in older Mexican adults: Looking beyond chronological aging

Abstract: BACKGROUND: COVID-19 has had a disproportionate impact on older adults. The population of Mexico is younger, yet the impact of COVID-19 on older adults is comparable to countries with older population structures. Here, we aim to identify health and structural determinants that increase susceptibility to COVID-19 in older Mexican adults beyond chronological aging. METHODS: We analyzed confirmed COVID-19 cases in older adults using data from the General Directorate of Epidemiology of Mexican Ministry of Health. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
9
0
2
Order By: Relevance
“…However, in previous studies conducted in Italy [28] and China [29], chronic obstructive pulmonary disease (COPD) was a significant predictor of mortality or factor of reaching the investigated outcomes. Contrary to that, Bello-Chavolla et al showed that COPD was only associated with hospitalization [24]. One of our study’s limitations is that the COVID-19 Register does not contain the data on pulmonary disease codes.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, in previous studies conducted in Italy [28] and China [29], chronic obstructive pulmonary disease (COPD) was a significant predictor of mortality or factor of reaching the investigated outcomes. Contrary to that, Bello-Chavolla et al showed that COPD was only associated with hospitalization [24]. One of our study’s limitations is that the COVID-19 Register does not contain the data on pulmonary disease codes.…”
Section: Discussionmentioning
confidence: 73%
“…These findings were confirmed in a nationwide study of 1,591 COVID-19 patients admitted to 26 hospitals in Italy [22] and in the US study of 1 305 patients [23]. In some contradiction with that, Bello-Chavolla et al, in their study addressing 20 804 COVID-19 patients aged 60 years and older, demonstrated that a combination of age and comorbidities was a better predictor of COVID-19 severity and mortality than age alone [24]. Our study included patients of all age groups, and according to our findings, a five-year increment of the age of enrolled patients increased the length of the hospital stay (HR 0.98), the risk of death (HR 1.12), the risk of the ICU transfer (OR 1.05), and the risk of IMV treatment (OR 1.05).…”
Section: Discussionmentioning
confidence: 83%
“…However, a preprint has found that, in older adults from Mexico, comorbidities or inequalities in accessing healthcare systems (difficulty in accessing a healthcare service or not having health insurance) are predictors of severity for COVID-19, regardless age. 27 Hence, it should be noted that some literature has reported that a significant Figure 1. Eligibility screening for systematic review.…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%
“…11 In Mexico, a COVID-19 lethality rate of 6.53% was found in the population over 60 years old. 12 Although in Brazil the age structure is not so old as in European countries, whereby elderly people account for 14.3% of the Brazilian population in 2020, nevertheless 52.7% of those aged 60 or over with COVID-19 have died. 8 This may be associated with the comorbidity profile of this population, as well as factors related to access to health care, alongside lack of public policies on active integration of the elderly in society, with low availability of programs providing healthier lifestyles for this population, thus making them more susceptible to pandemic situations like this one.…”
Section: Discussionmentioning
confidence: 99%